Tinjauan Ekonomi Syariah Dalam Sewa Menyewa Produk IndiHome Di PT. Telkom Kandatel Purwakarta - Luthfi Rahman; Asep Dede Kurnia; Saepul Bahri; Ahmad Ali Sopian (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2021)
Telkom is a state-owned company engaged in telecommunications and network services in the territory of Indonesia. One of the products from Telkom is IndiHome. In IndiHome, the company's agreement system with consumers is to rent tools or devices for consumers to use to connect with IndiHome, then consumers pay monthly to extend the lease. Based on the basic provisions of the theory in Islam that leasing is a form of muamalah activity in meeting the needs of human life, in the sharia economic concept, leasing is called (al-ijarah), which has the pillars and conditions that become the legal provisions of the ijarah contract. The purpose of this study was to determine the practice of renting IndiHome at PT. Telkom Indonesia Kandatel Purwakarta and to find out an overview of the sharia economy in leasing indihome products at PT. Telkom Kandatel Purwakarta. The type of research used is field research, while the approach used in this research is a descriptive-qualitative approach. The mechanism used in leasing IndiHome has provisions according to company procedures. The transaction process is carried out with customer registration via offline, carried out directly and online through the My IndiHome application and Call Center to PT.Telkom and if viewed in the sharia economy, IndiHome leases are included in leases that are not in accordance with the provisions of the Fatwa of the National Sharia Council of the Ulama Council. Indonesia No. 112/DSN-MUI/IX/2017, including those related to mu'jir provisions that are not legally competent, provisions on benefits of objects that cannot be leased back and unclear rental times.